Uso del suelo y grado de cobertura vegetal en una cuenca del centro de la provincia de Buenos Aires (Cuadernos del CURIHAM is a half-year publication of the Centro Universitario de Rosario of hydro-environmental research directed by Adelma Mancinelli. It is dedicated to spreading the results of basic and applied research as well as technological innovations on the realm of hidro-environmental issues. It may include field study results, interdisciplinary studies or studies on the state of art on the field: basic hydraulics, fluvial and hydrodinamics, superficial and underground hydrology, urban and stochastic hydrology, planning and management of hydric resources, environmental evaluation, pollution and quality of the water, politics and water legislation, regional hydro-environmental management, hydraulic construction, methods and techniques and everything related to hydro-environmental sciences., 2007)
The agricultural land use and the degree of vegetal cover are important parameters to consider the potentiality of runoff and erosion in a basin and, in addition, to evaluate the development of crops, production, etc. In this work the variation of the land use and the vegetal cover throughout a year (April of 2005 until March of 2006) in a cattle agricultural river basin of the center of the Buenos Aires province, Argentina, is evaluated. This annual cycle, while modifications of productive structure of the zone do not take place, can be valid for many years. In order to obtain the desired objective, techniques of digital processing of satellite images and GIS are used. Thus the land use is determined by means of nonsupervised classification of the images. Then, to each use a percentage of cover is assigned according to field measurements and to the phenologic state, in the case of crops. 12 land use categories throughout the year are obtained, to which lagoons, rock outcrops and forest are added. The results show minor degrees of cover in winter, with a minimum of 66 % in September, and then grow until to reach a maximum of 92 % in February and March, in the apogee of the cultures of soybean and maize.
Keywords: Vegetal cover; Land use; Remote sensing